Assédio de gênero na caserna: a judicialização e o controle interno das práticas de assédio moral envolvendo mulheres policiais militares da Paraíba - Alves, Geni Francinelle dos Santos (2018)
Symbolic violence called moral harassment, which unfolds from causes that generate sociocultural, economic and, especially psychological consequences, has aroused the interest of society, especially from a socio-juridical perspective. From the nineties, the phenomenon has spread with the intense production of studies around the world. However, although widely debated and discussed, it is noted that the growth of bullying in the workplace shows that forms of prevention and coercion are still insufficient. From this perspective, the phenomenon of bullying must be thought beyond a merely interpersonal approach in which only the personal factors of the parties involved, such as the perversion of the stalkers and the fragility and intrinsic qualities of the victims, are at stake, to launch an interdisciplinary look that can encompass factors other than moral. In this sense, in understanding the gender relations and power experienced in the labor market, the singular form in which the female presence has gained ground in militarized institutions, whether in the Armed Forces or in the military police, stands out in a certain way emerged as a topic of expanding studies in Brazil, particularly in the field of social sciences. Aimed at reflecting on the objective and symbolic aspects that mark women's work in traditionally masculine spaces, this dissertation analyzes the practices of moral harassment in the light of Marie-France Hirigoyen's theory on possible cases of moral harassment involving women in the Military Police of Paraíba. This study, therefore, seeks to reflect, by conducting in-depth interviews with 10 female military police officers with different service times and various hierarchical circles, as well as through field research and documentary analysis, such as the Military Penal Code and the Disciplinary Regulations are applied in concrete cases, seeking to demonstrate their effectiveness under the tutelage of the legaladministrative-disciplinary field. What is evident in this process is that the importance given by the legal and administrative sphere to the moral conditions imposed by the military culture and its normalizing character ends up triggering as an institutional consequence: a greater relevance given to the breaking of moral-disciplinary principles to the detriment of more that resemble bullying. If on the one hand the Military Police of Paraíba is based on the principles of hierarchy and discipline to guide the social practices of command and obedience established among its members, on the other hand the relations of power are internalized from customs, traditions, explicit laws or implicit, that conceal and make invisible certain violent practices, hitherto naturalized in the military environment, and which, in a certain way, constitute moral harassment. In addition to serving as a reference for new reflections in the military sphere, the study aims to stimulate a new management perspective with more humanized and conscious relationships, as well as the application of institutional policies focused on practices of respect and professionalism.